2015
DOI: 10.1016/j.brainres.2014.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Use of biomarkers in ALS drug development and clinical trials

Abstract: The past decade has seen a dramatic increase in the discovery of candidate biomarkers for ALS. These biomarkers typically can either differentiate ALS from control subjects or predict disease course (slow versus fast progression). At the same time, late-stage clinical trials for ALS have failed to generate improved drug treatments for ALS patients. Incorporation of biomarkers into the ALS drug development pipeline and the use of biologic and/or imaging biomarkers in early- and late-stage ALS clinical trials ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 134 publications
0
26
0
Order By: Relevance
“…Direct infusion of Actemra into patients has been shown to decrease mRNA expression of many inflammatory cytokines in the serum of patients with sALS with high basal inflammation both acutely and longitudinally, and this correlated with attenuated decrease in ALSFRS-R scores [161]. Further studies utilizing Actemra in phase II clinical trials is already planned and will need to be performed in order to validate fully its effects [167]. Prior studies identified up to a 10-fold increase in the prostaglandin E2 levels in the CSF of patients with ALS as compared with healthy control patients [51,52].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Direct infusion of Actemra into patients has been shown to decrease mRNA expression of many inflammatory cytokines in the serum of patients with sALS with high basal inflammation both acutely and longitudinally, and this correlated with attenuated decrease in ALSFRS-R scores [161]. Further studies utilizing Actemra in phase II clinical trials is already planned and will need to be performed in order to validate fully its effects [167]. Prior studies identified up to a 10-fold increase in the prostaglandin E2 levels in the CSF of patients with ALS as compared with healthy control patients [51,52].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Pharmacodynamic biomarkers to evaluate disease progression and response to therapy are needed for studies in motor neuron diseases, including amyotrophic lateral sclerosis (ALS) and spinal muscular atrophy (SMA) for both preclinical animal testing and in human clinical trials (1,2). Effective biomarkers could offer greater sensitivity to drug effects than standard outcomes measures such as the ALS Functional Rating Scale-Revised, strength testing, timed functional tests (such as the 6-minute walk) and forced vital capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing a combination of multiple anti-TDP-43 scFvs may prove valuable in providing a personalized diagnosis for each patient in both sporadic and familial ALS cases. A personalized blood-based diagnosis system could also be very helpful for initiating and monitoring treatment strategies for ALS [41, 42]. …”
Section: Discussionmentioning
confidence: 99%